Study of the Influence of Variation in Distances Between Electrodes in Spectral DBD Plasma Excitation - Ivan Alves de Souza; Arlindo Balbino do Nascimento Neto; José César Augusto de Queiroz; Efrain Pantaleón Matamoros; Thércio Henrique de Carvalho Costa; Michelle Cequeira Feitor; John Magno Lopes de Souza; Nailton Torres Camara; Valmar da Silva Severiano Sobrinho (Materials Research, 2016)
Dielectric Barrier Discharge (DBD) is a promising technique for producing plasma in atmospheric pressure and is gaining emphasis in several areas, especially in the biomedical and textile industries, among other. This is due to the fact that this plasma does not reach high temperatures, enabling its use on thermally sensitive materials. However, there is still the need for the development of research relating to the field of physical mechanisms of non-thermal plasma. In this work, we studied the behavior of plasma in DBD equipment, varying distance between electrodes. For this study, two distinct characterization techniques were used. The first, the Lissajous Figures method, is effective and precise in the electrical characterization of DBD equipment. The second technique used, Optical Emission Spectroscopy (OES) is an effective tool in the diagnosis of plasma. This tool enables the identification of excited species in plasma. With the data produced, it was possible to identify an appropriate distance for producing plasma with a higher intensity and homogeneity of active species.